Prospects for the Role of Ferroptosis in Fluorosis - Zhang, Yi; Wu, Jialong; Jiang, Lai; Lu, Chenkang; Huang, Zhengwei; Liu, Bin (Frontiers in Physiology, 2021)
As a strong oxidant, fluorine can induce oxidative stress resulting in cellular damage. Ferroptosis is an iron-dependent type of cell death caused by unrestricted lipid peroxidation and subsequent plasma membrane rupture. This article indicated a relationship between fluorosis and ferroptosis. Evidence of the depletion of glutathione and increased oxidized glutathione can be found in a variety of organisms in high fluorine environments. Studies have shown that high fluoride levels can reduce the antioxidant capacity of antioxidant enzymes, while increasing the contents of reactive oxygen species and malondialdehyde, resulting in oxidative stress and fluoride-induced oxidative stress, which are related to iron metabolism disorders. Excessive fluorine causes insufficient GSH, GPX4 inhibition, and oxidative stress, resulting in ferroptosis, which plays an important role in the occurrence and development of fluorosis.